Rancangan Guru Dalam Pembelajaran Pendidikan IPS Di Era Digital - Safran Safran; Adil Rosyadi Hasibuan; Omega Megarani; Fitri Ramadhani (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The rapid progress of digital technology has brought major changes in various areas of life, including education. With the increasing importance of digital literacy as we grapple with the digital era, it is important to assess the suitability of curricula based on digital literacy requirements. The aim of this research is to analyze the suitability of the social studies curriculum to digital literacy needs. This study used a qualitative research approach to conduct a comprehensive literature review to explore existing literature on integrating digital literacy into social studies education curricula. A variety of sources, including academic articles, books, and curriculum guides, were reviewed and a match between the curriculum and current digital literacy requirements was identified. The results of this research reveal several important aspects regarding the suitability of the curriculum to digital literacy needs. Accordingly, curricula for social science education must strengthen the integration of digital competency concepts, provide appropriate training and support for teachers, incorporate collaborative activities using technology, and develop the provision of high-quality digital resources. Collaboration between schools, industry and digital communities can also enrich the curriculum with real-world experiences and current practices related to digital literacy.